2011
DOI: 10.3109/13625187.2011.614028
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel releasing-intrauterine system for the treatment of menorrhagia and/or frequent irregular uterine bleeding associated with uterine leiomyoma

Abstract: The LNG-IUS is effective in controlling heavy menorrhagia and/or frequent irregular uterine bleeding related to the presence of myomas, but has no significant effect on the size of the tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Similarly, in the study by Socolov et al .,[3] 89% of women with fibroids considered LNG IUS as a good treatment.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly, in the study by Socolov et al .,[3] 89% of women with fibroids considered LNG IUS as a good treatment.…”
Section: Discussionmentioning
confidence: 74%
“…A study by Socolov et al .,[3] evaluating LNG IUS use in menorrhagia due to fibroids showed that 96% of the patients had achieved oligomenorrhea by 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hemoglobin levels increased by 2 g/dL in the LNG-IUD group compared to 0.1 g/dL in the COC group. Another prospective study of 102 women with leiomyomas and AUB-L administered the LNG-IUD to all subjects [ 14 ]. The primary outcome, menstrual bleeding, decreased signifi cantly over the year of the study, with 89 % of participants being satisfi ed with the LNG-IUD.…”
Section: Abnormal Uterine Bleedingleiomyomata (Aub-l)mentioning
confidence: 99%
“…Women, therefore, need some therapy to tide over this difficult time. Levonorgestrel intrauterine system (LNG IUS) is a nonsurgical, long acting, alternative to the traditional medical and surgical treatments that is one such feasible option in these women [4][5][6].…”
Section: Introductionmentioning
confidence: 99%